Exploring 5-Benzylthiazolidine-2, 4-Dione Derivatives as Promising PPAR-gamma Agonists through Computational Methods - Gyampoh, Solomon; Nabi, Minnatullah; Arora, Pinky; Kumar, Shubham (Current Signal Transduction Therapy, 2025)
IntroductionPeroxisome Proliferator-Activated Receptors (PPARs) are nuclear receptors involved in the regulation of glucose and lipid metabolism, making them potential targets for treating type 2 diabetes mellitus. 5-Benzylthiazolidine-2, 4-dione derivatives, organic compounds with a thiazolidine-2, 4-dione core and a benzyl moiety at the 5-position, have garnered attention for their diverse pharmacological activities, including anti-inflammatory, anti-cancer, anti-diabetic, anti-tubercular, and anti-viral properties.MethodsThis research aimed to identify 5-benzylthiazolidine-2,4-dione derivatives as synthetic PPAR-gamma agonists using computational methods, such as molecular docking and in silico ADMET analysis. Virtual screening generated potential molecules, and molecular docking studies using AutoDock Vina 1.5.6 were performed at the active site of the PPAR-gamma receptor (PDBID: 4PRG).ResultsNine hits were identified based on their binding affinities and were further evaluated using SwissADME for their ADME properties. These nine compounds demonstrated superior ADME profiles and bioavailability compared to the standard drug Rosiglitazone.ConclusionThis study provides a comprehensive computational approach for discovering novel PPAR-gamma receptor agonists, potentially advancing experimental diabetes research.
Keywords: PPAR-gamma receptor